Distinct early life stage gene expression effects of hybridization among European and North American farmed and wild Atlantic salmon populations. Issue 9 (17th March 2022) - Islam, Shahinur S.; Xue, Xi; Caballero‐Solares, Albert; Bradbury, Ian R.; Rise, Matthew L.; Fleming, Ian A.
Abstract: Due to multigeneration domestication selection, farmed and wild Atlantic salmon diverge genetically, which raises concerns about potential genetic interactions among escaped farmed and wild populations and disruption of local adaptation through introgression. When farmed strains of distant geographic origin are used, it is unknown whether the genetic consequences posed by escaped farmed fish will be greater than if more locally derived strains are used. Quantifying gene transcript expression differences among divergent farmed, wild and F1  hybrids under controlled conditions is one of the ways to explore the consequences of hybridization. We compared the transcriptomes of fry at the end of yolk sac absorption of a European (EO) farmed ("StofnFiskur", Norwegian strain), a North American (NA) farmed (Saint John River, NB strain), a Newfoundland (NF) wild population with EO ancestry, and related F1  hybrids using 44 K microarrays. Our findings indicate that the wild population showed greater transcriptome differences from the EO farmed strain than that of the NA farmed strain. We also found the largest differences in global gene expression between the two farmed strains. We detected the fewest differentially expressed transcripts between F1  hybrids and domesticated/wild maternal strains. We also found that the differentially expressed genes between cross types over‐represented GO terms associated with metabolism, development, growth, immune response, and redox homeostasis processes. These findings suggest that the interbreeding of escaped EO/NA farmed and NF wild population would alter gene transcription, and the consequences of hybridization would be greater from escaped EO farmed than NA farmed salmon, resulting in potential effects on the wild populations.